2020
DOI: 10.7717/peerj.10499
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory effect of obesity on rats with burn wounds

Abstract: Objective A burn is an inflammatory injury to the skin or other tissue due to contact with thermal, radioactive, electric, or chemical agents. Burn injury is an important cause of disability and death worldwide. Obesity is a significant public health problem, often causing underlying systemic inflammation. Studying the combined impact of burn injuries on obese patients has become critical to the successful treatment of these patients. The aim of this paper is to highlight the effect of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our study found that the expression of inflammatory factors in the obese groups with burn injuries was higher than the burn groups with normal weight, which was consistent with a previous study by our team. 28 We observed a tendency of first fast then slow of skin wound healing after burns were inflicted. There were no animal mortalities during the study period.…”
Section: Discussionmentioning
confidence: 95%
“…Our study found that the expression of inflammatory factors in the obese groups with burn injuries was higher than the burn groups with normal weight, which was consistent with a previous study by our team. 28 We observed a tendency of first fast then slow of skin wound healing after burns were inflicted. There were no animal mortalities during the study period.…”
Section: Discussionmentioning
confidence: 95%
“…Elevated C-reactive protein, interleukin-10, adiponectin, and leptin are found in obese patients after surgery. 20 However, there is little research focusing on the effect of overweight and obesity on the surgical procedure itself.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, obesity is considered to be associated with stronger systemic inflammation, inducing worse postoperative outcomes. Elevated C-reactive protein, interleukin-10, adiponectin, and leptin are found in obese patients after surgery 20. However, there is little research focusing on the effect of overweight and obesity on the surgical procedure itself.…”
Section: Discussionmentioning
confidence: 99%